Estimation of stability derivatives of an oscillating hypersonic delta wings with curved leading edges - Crasta, Asha; Khan, Sher Afghan (International Association of Engineering and Management Education (IAEME), 2012)
In the present study hypersonic similitude has been used to obtain stability derivatives in pitch and roll of a delta wing with curved leading edges for the attached shock case. A strip theory is used in which strips at different span-wise locations are independent. This combines with the similitude to give a piston theory. The present theory is valid only for attached shock case. Effects of wave reflection and viscosity have not been taken into account. Some of the results have been compared with those of Hui et al, Ghosh and Liu & Hui. Results have been obtained for hypersonic flow of perfect gas over a wide range of mach numbers, incidences and sweep angles.